A Multicriteria Decision Support Methodology for Evaluating Airport Expansion Plans - Ron Vreeker; Peter Nijkamp; Chris Ter Welle (Tinbergen Institute, 2001)
Rational decision-making requires an assessment of advantages and disadvantages of choicepossibilities, including non-market effects (such as externalities). This also applies to strategicdecision-making in the transport sector (including aviation). In the past decades various decisionsupport and evaluation methods have been developed in which a market evaluation played aprominent role. The intrinsic limitations of these approaches were also increasingly recognised.Gradually, a variety of adjusted multidimensional methods has been developed over the pastyears to complement conventional Cost-Benefit Analysis. These methods aim to investigate andevaluate all relevant impacts of a choice possibility (e.g., project, plan, or programme) on the basisof a multitude of important policy criteria (so-called multicriteria methods). They have a particularrelevance in case of non-priced or qualitative effects.There is a clear need for a systematic and polyvalent multicriteria approach to many actualplanning issues, such as land use or transportation. This paper offers a new evaluation frameworkbased on a blend of three types of approaches, viz. Regime Analysis (an advanced pairwisecomparison method), the Saaty method (an analytical hierarchical procedure for preferencestatements) and the Flag Model (based on critical threshold value analysis). All these methods havebeen developed separately in the past; the paper makes an effort to offer a cohesive framework,which can be used for the evaluation of spatial-economic and environmental-economic policyissues.This new tool is tested by means of a case study on conflicting plans (and policy views) forairport expansion options in the Maastricht area in the Southern part of the Netherlands.
Keywords: 330; Flughafen; Management-Informationssystem; Investitionsrechnung; Theorie; Maastricht